Etiology and Control of Blight and Fruit Rot of Brinjal - Jenny John (Department of Plant Pathology, College of Agriculture, 1991)
The present investigation was undertaken to evolve an economically feasible management practice against the fruit rot and twig blight of brinjal. Infected plant parts of brinjal showing initial stages of infection were collected from different localities and symptomatology of the pathogen was studied in detail. The pathogen was brought into pure culture and sent to C.M.I. International Mycological Institute, U.K. for identification. It was identified to be Phomopsis vexans (Sacc. & Sydow.) Harter. Pathogenicity of the fungus was studied by inoculating the fruits and stems of the host plants and typical symptom similar to natural conditions were observed. Host range of the pathogen was studied by inoculating the different vegetables with the test fungus. Only carrot and tomato was found susceptible to the pathogen. The fungus grew well equally on potato dextrose host extract and oat meal media followed by Czapek’s and Richards’s media. Good sporulation of the fungus was also noticed in potato dextrose and host extract media, fair sporulation in oat meal and Czape’ks media and no sporulation in Richards’s media. In some cases wavy growth of the pathogen was noticed in potato dextrose agar. In liquid media good mycelia growth of the fungus was observed in potato dextrose, host extract and Czapek’s followed by oat meal and Richard’s media. Culture filtrate of the fungus caused drying of the leaves of the young seedling kept dipped in it and on leaves of matured plants it developed dark brown spots and these leaves dried up eventually. Seed treatment with culture filtrate exerted an inhibitory effect on germination of seeds of brinjal, chilli, tomato and greengram, whereas germination percentage was above 90 in seeds kept in sterile water. There was no difference in germination of seeds treated with culture filtrate fresh and that which was boiled for 10 minutes. The germination of seeds greatly reduced in seeds extracted from infected fruits both in blotter and sand method whereas the germination percentage of seeds extracted from healthy fruit was above 90 per cent. The seedlings raised from infected fruit showed damping off symptom after 2 weeks. Laboratory evaluation of different fungicides revealed that all the fungicides could inhibit the growth of the pathogen. Bordeaux mixture gave complete inhibition of growth of fungus at 750 ppm concertation while bavistin had the same effect at 500 ppm concentration. In field evaluation with different fungicides to control Phomopsis fruit rot it was found that spraying with CoC-50 at fortnightly interval was the best fungicide as the per cent infected fruits were minimum, that is 3.9, followed by Bordeaux mixture, dithane M-45, kavach, calixin, bavistin, and cumin L, with per cent infected fruits being 8.95, 10.7, 14.64, 15.35, 17.04, 20.56 respectively. Seeds of brinjal when soaked in spore suspension for 24 hours showed a reduction in germination compared to those seeds soaked in sterile water for the same period. Seed treatment with different fungicides showed that bavistin was the best fungicide in inhibiting the effect of the pathogen on seed germination followed by dithane M-45, and COC -50.